Use of early non-invasive artificial ventilation in full term newborns with moderate and severe hypoxic ischemic encephalopathy - O. Yu. Klievakina; I. O. Anikin (Patologìâ)
The search for and use of alternative respiratory support strategies is promising to improve both close and distant nursing outcomes for newborns with hypoxic ischemic encephalopathy (HIE).